2018
DOI: 10.1051/shsconf/20185407008
|View full text |Cite
|
Sign up to set email alerts
|

Sex Massage Therapy at Spa: A New Form of Prostitution

Abstract: Sex massage therapy is a new form of prostitution and it becomes one of the commodities in the sex tourism. Sexual service activities carried out under the guise of massage therapies at spa. This condition will disturb security and order. Prostitution is not just a legal issue, but also a moral issue. Sex massage therapy at spa becomes a form of covert prostitution. Activities sexual services are made as if as a medical therapy by taking refuge in the legal business. Unfortunately, this fake spa is untouched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The third ambiguous space in which sexual exploitation of minors occurs in Bali are spa massage parlours. Under the guise of the legal umbrella of a spa massage parlour, additional sex services are provided to customers (Wiryawan & Bunga 2018). The massages offered in these ‘spa plus’ parlours by underaged therapists – most of whom are female, though there are also some young men (ibid.)…”
Section: Ambiguous Spaces and Cst In Balimentioning
confidence: 99%
See 2 more Smart Citations
“…The third ambiguous space in which sexual exploitation of minors occurs in Bali are spa massage parlours. Under the guise of the legal umbrella of a spa massage parlour, additional sex services are provided to customers (Wiryawan & Bunga 2018). The massages offered in these ‘spa plus’ parlours by underaged therapists – most of whom are female, though there are also some young men (ibid.)…”
Section: Ambiguous Spaces and Cst In Balimentioning
confidence: 99%
“…Our research revealed two types of recruitment processes: the first involves minors who know that the spa offers additional sexual services, while the second involves minors who are promised a good job in a spa and do not know in advance about the sexual services. In the latter case, the minors only find out once they start the job, at which point they are already in debt with the spa owner (Wiryawan & Bunga 2018, p. 2). Working in Bali's tourism industry offers prestige and economic benefits (Howe 2006, p. 9).…”
Section: Ambiguous Spaces and Cst In Balimentioning
confidence: 99%
See 1 more Smart Citation
“…This underground and discreet activity of male masseurs is unknown to the general public. Thereby sex massage therapy is disguised as prostitution (Wiryawan & Bunga, 2018;Tayibnapis et al, 2019;Matolcsi et al, 2021;Monk-Turner & Turner, 2017).…”
Section: Introductionmentioning
confidence: 99%